2021
DOI: 10.3389/fpubh.2021.687048
|View full text |Cite
|
Sign up to set email alerts
|

Adoption Intention and Factors Influencing the Use of Gerontechnology in Chinese Community-Dwelling Older Adults: A Mixed-Methods Study

Abstract: Objective: To explore the Chinese community-dwelling intention of older adults to adopt gerontechnology and its influencing factors.Design: A mixed-methods sequential explanatory design with an inductive approach was employed. In phase 1, a self-made questionnaire was administered from August 2018 to December 2019. Multifactor logistic regression was used to analyze the adoption intention and factors influencing the use of gerontechnology. In phase 2, participants completed a semistructured interview to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…First of all, research regarding technology adoption by design receives less attention in the field of DfDI, as the co-occurrence keywords "adoption" or "technology adoption" appear with significantly smaller dots (Figure 4). Existing literature regarding technology adoption could be abundant [54][55][56][57][58], but research regarding how to foster adoption by design is still insufficient. Without promoting the motivation for adoption, there will be no further usage of inclusive digital products or services among users.…”
Section: Research Gaps and Future Directions On Dfdimentioning
confidence: 99%
“…First of all, research regarding technology adoption by design receives less attention in the field of DfDI, as the co-occurrence keywords "adoption" or "technology adoption" appear with significantly smaller dots (Figure 4). Existing literature regarding technology adoption could be abundant [54][55][56][57][58], but research regarding how to foster adoption by design is still insufficient. Without promoting the motivation for adoption, there will be no further usage of inclusive digital products or services among users.…”
Section: Research Gaps and Future Directions On Dfdimentioning
confidence: 99%
“…This is a problem that leads us to ask if said group finds this technology useful, a question that does not have a clear solution and answer as research on these issues has been scarce to date and studies published yield contradictory results. On one hand, authors such as Martı ´n and Marcos (2017), Sunkel and Ullman (2019) or Huang et al (2021) argue that older adults perceive technology as increasingly positive. Meanwhile on the other hand, researchers such as Gonz alez On ˜ate and Fanjul Peyr o (2018) or Seifert et al (2018) have observed that older adults state that these technologies do not appear to be adapted to their needs and demand, making them feel uncomfortable and ill prepared for its use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on a report entitled “Technology for Adaptive Aging” by the US National Research Council (2003), literature consistently points out (Chen and Chan, 2014; Pew and Van Hemel, 2004; Martín-García, 2021b) that these technology environments, products and services are divided into five areas of development called “life domains”: Living Environments; Communication; Personal mobility and transportation; Health; and Employment, Education, Recreation or self-fulfillment. As the goal of each of these fields is to prevent, compensate or improve accessibility and usability of these products to improve the daily life of the elderly, specialist literature simplifies these areas into different categories according to their use (Huang et al , 2021; Sundgren et al , 2020) like gathering continuous data; assisting older people cognitively and socially; providing care or monitoring of health from a distance; compensating for possible technology deficits in the home environment; or into different domains based on their similarities in terms of goals or context of use (Chen and Chan, 2014); home and daily living, communication, health care, education and recreation. In this study, gerontechnology is used as an umbrella term for all of the technologies mentioned in these five main areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their findings revealed that age, the number of children, the frequency of children visiting their parents, self-rated health, the presence of chronic diseases, and attitudes toward smart senior care significantly influence older individuals' willingness to choose smart senior care services. (21). In summary, existing research generally acknowledges that factors such as gender, age, number of children, living arrangements, economic affordability, healthcare and senior care security, self-rated health status, the presence of chronic illnesses, and awareness of smart senior care can influence the demand for smart senior care among the older adults.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that age, living conditions, and physical health significantly affect the acceptance of smart senior care services among the older adults. Huang et al ( 21 ) investigated the usage intentions of 1,180 older residents in 12 communities in Chongqing regarding smart products. They discovered that factors such as gender, education level, marital status, monthly income, type of health insurance, self-rated health, and the presence of chronic diseases influence the willingness of the older adults to use smart products ( 21 ).…”
Section: Introductionmentioning
confidence: 99%